Children and M-Commerce: some social and legal issues - Ab Rahman, Suhaimi; Md Khalid, Rasyikah (Center for Enhancing Knowledge, 2013)
Mobile-culture among children and young person is happening all around the world. For the new generation, mobile phones are not only a devise to make calls, but rather as an instrument for coordinating their social life. SMS, MMS, games, music, and videos are features available on the mobile phones and teenagers are their main players. Little that they know that these activities are part of a new way commerce is carried out. Mobile commerce or M-Commerce is gr owing but its impacts on the young generation can be tremendous. This short article aims at highlighting possible issues that may arise with regard to minors and M-Commerce. Special reference has been made to the legal positions in Malaysia with regard to contractual issues arising from M-Commerce.